The assessment on sustainable operation and procedures for rural road maintenance in Tanjung Malim: with the provision of JKR green criteria / Muhammad Iqbal Abdullah - Abdullah, Muhammad Iqbal (2021)
Malaysia is making progress toward implementing a green highway and rural road system. Green road rating tools such as the Malaysia Green Highway Index (MyGHI) for highways and Penarafan Hijau (pHJKR Jalan) for non-toll roads with a project value of more than RM50 million are examples of green efforts made in Malaysia to promote sustainable development. The main aim of this research is to assess the sustainable operation and maintenance procedure of rural road in Tanjung Malim based on JKR Green Criteria provision. The problem statement elaborates on how Malaysian lack of implementing regarding the sustainable operation and procedures for rural road. In order to comply with the objective of this research, two (2) case studies have been chosen to participate in comparison observation and three (3) agency which is government (Tanjung Malim district Council), private (Puncak Emas Infra Sdn. Bhd) and other contractors. This research is consisting of five main (5) chapters which is chapter one (1) Introduction where it refers the aim, the objectives and problem, method and significance, chapter two (2) Literature Review which elaborates the background study of rural road in Malaysia, chapter three (3) Research Methodology presenting the approach of the research, the research design, sampling, data collection, elaboration on case studies, and data analysis, chapter four (4) Results and Discussion elaborates on the analysis of the data that had been obtained from the respondents based on the method and their demographic background, lastly chapter five (5) Conclusions on the data analysis that has been made for this study